Anato-morphological and chemical characterization of bamboo (Guadua amplexifolia J. Presl) from San Jorge River Basin, Colombia - Yiniva Camargo Caicedo; Jorge Augusto Montoya Arango; Andrés Prieto Muriel (Cleaner Engineering and Technology)
Studying bamboo species' anato-morphological characteristics and chemical composition is crucial for identifying potential uses and comparing the species′ properties. Guadua amplexifolia J. Presl is a promising bamboo species that has been underrepresented in research regarding its properties. To determine its potential applications, this study focuses on the anatomical, morphological, and chemical properties of Guadua amplexifolia J. Presl in the San Jorge River basin. Four-and five-year-old Guadua amplexifolia J.Presl bamboo culms were divided into three sections, lower, middle, and upper, to facilitate the characterization of their anatomical and chemical properties. The anato-morphological characterization included measuring internode length and diameter, wall thickness, and internode density, vascular bundle density, length and distribution, fiber density, and wall thickness. Meanwhile, the chemical analysis involved proximate and elemental analysis, as well as lignocellulosic composition, to determine Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF), Alkaline Lignin Fiber (ALF), and Extractable Ether (EE). The internodes of the analyzed samples exhibited thick walls with either small or absent lacuna, and some culms were notably solid at the lower part, both of which are significant for identification purposes. The vascular bundles in the internal and transitional zones of the walls were oriented randomly. Furthermore, the analysis of the lignocellulosic composition of Guadua amplexifolia J. Presl revealed that water content, NDF, ADF, and ALF increase from lower to upper sections. The distribution of vascular bundles directly influences the chemical properties of the bamboo.